PENYULUHAN PENGEMBANGAN PERPUSTAKAAN DESA TERAUTOMASI BERBASIS SLiMS DI PERPUSTAKAAN DESA DEMANGREJO KULON PROGO - MURSYID, MOH.; ERNAWATI; WIWIN IRPINA; MUHAMMAD LUTHFI HIDAYAT (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2024)
Background: Technological advancements have influenced various aspects of life, including libraries. Village libraries, as the frontline providers of information access in rural areas, are required to adapt to current technological developments. To strengthen information technology (IT) capabilities, the library and information science study program conducted a community service activity at the Demangrejo Village Library in Kulon Progo. This activity involved providing counseling to library managers on the development of automated village libraries based on SLiMS. Objective: This counseling program aims to enhance understanding and knowledge related to library development through the implementation of SLiMS-based automation systems, as well as to improve the skills of library staff in operating these systems. Method: The counseling activity was conducted by delivering material to participants in the form of PowerPoint presentations and discussions related to the development of SLiMS-based automated village libraries. Results: The counseling results showed an increase in participants' understanding of the development of SLiMS-based automated village libraries. Participants recognized that library automation makes the work of library managers easier, such as cataloging, circulation, and reporting. Consequently, library managers have sufficient time to serve library users optimally. Moreover, automation can also improve information access and literacy in rural communities.